Legal Certainty in Electronic Contracts for E-Commerce Transactions in Indonesia - Ade Pratiwi Susanty (Westscience Press, 2026)
The rapid expansion of e-commerce in Indonesia has led to the extensive use of electronic contracts as the primary legal instrument governing digital transactions. This development raises important legal issues related to legal certainty, particularly concerning the validity, enforceability, evidentiary value, and protection of parties involved in electronic contracts. This study aims to analyze legal certainty in electronic contracts within e-commerce transactions in Indonesia using a normative juridical approach. The research examines statutory regulations, legal principles, and doctrines related to contract law, electronic transactions, and consumer protection. The findings indicate that Indonesian law has formally recognized electronic contracts as legally binding and has acknowledged electronic documents as valid evidence. However, several challenges remain, including ambiguity in electronic consent, limitations in authentication mechanisms, evidentiary reliability, and the imbalance of bargaining power between business actors and consumers. The lack of full harmonization between traditional contract law and electronic transaction regulations also affects the predictability and consistency of legal enforcement. This study concludes that while the existing legal framework provides a basic level of legal certainty, further normative refinement and regulatory harmonization are necessary to strengthen legal protection and enhance trust in e-commerce transactions in Indonesia.